2023
DOI: 10.3389/fphys.2023.1099278
|View full text |Cite
|
Sign up to set email alerts
|

Dual thick and thin filament linked regulation of stretch- and L-NAME-induced tone in young and senescent murine basilar artery

Abstract: Stretch-induced vascular tone is an important element of autoregulatory adaptation of cerebral vasculature to maintain cerebral flow constant despite changes in perfusion pressure. Little is known as to the regulation of tone in senescent basilar arteries. We tested the hypothesis, that thin filament mechanisms in addition to smooth muscle myosin-II regulatory-light-chain-(MLC20)-phosphorylation and non-muscle-myosin-II, contribute to regulation of stretch-induced tone. In young BAs (y-BAs) mechanical stretch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The disparities between our results and those reported by others ( Barton et al, 1997 ; Lubomirov et al, 2016 ; 2018 ; 2021 ; Luttrell et al, 2020 ; Zhong et al, 2021 ) could be due to differences in species (rat vs. mouse), strain of animal and/or vessel studied. In addition, MYPT1 has multiple phosphorylation sites which regulate MLC phosphatase activity ( Somlyo and Somlyo, 1994 ; Hartshorne et al, 1998 ; Brozovich et al, 2016 ), and in murine basilar arteries, others have demonstrated that MYPT1 phosphorylation at T853 increases during aging ( Lubomirov et al, 2023 ). We did not measure MYPT1 phosphorylation, and changes in MYPT1 phosphorylation could contribute to the disparities among studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The disparities between our results and those reported by others ( Barton et al, 1997 ; Lubomirov et al, 2016 ; 2018 ; 2021 ; Luttrell et al, 2020 ; Zhong et al, 2021 ) could be due to differences in species (rat vs. mouse), strain of animal and/or vessel studied. In addition, MYPT1 has multiple phosphorylation sites which regulate MLC phosphatase activity ( Somlyo and Somlyo, 1994 ; Hartshorne et al, 1998 ; Brozovich et al, 2016 ), and in murine basilar arteries, others have demonstrated that MYPT1 phosphorylation at T853 increases during aging ( Lubomirov et al, 2023 ). We did not measure MYPT1 phosphorylation, and changes in MYPT1 phosphorylation could contribute to the disparities among studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SM myosin, NM myosin is regulated by phosphorylation of its light chain ( Cremo et al, 2001 ). Further, NM myosin phosphorylation is regulated during contraction of smooth muscle ( Yuen et al, 2009 ; Zhang and Gunst, 2017 ) and NM myosin has been demonstrated to participate in force maintenance ( Morano et al, 2000 ; Löfgren et al, 2003 ; Rhee et al, 2006 ; Yuen et al, 2009 ; Zhang and Gunst, 2017 ; Lubomirov et al, 2023 ); both a change in NM myosin expression ( Morano et al, 2000 ; Löfgren et al, 2003 ; Yuen et al, 2009 ) and inhibition of the NM myosin AMATPase ( Rhee and Brozovich, 2003 ; Lubomirov et al, 2023 ) have been demonstrated to produce a reduction in force, which demonstrate that changes in NM myosin expression will alter force. In tertiary mesenteric vessels, during aging, our data show NM myosin expression is reduced by ∼10% ( Figure 2 ), while there is no change in NM myosin expression in the aorta, a large conduit vessel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations